Analisis Pengaruh Angkatan Kerja, Angka Melek Huruf, Angka Putus Sekolah Dalam Disparitas Anggaran Pendidikan - Saputri, Novi Ani Ajeng; Ismanto, Bambang; Santoso, Tri Nugroho Budi (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The study aims to determine the effect of the labor force on the education budget, between the literacy rate on the education budget, and between the dropouts rate on the education budget. This research is a quantitative study with multiple linear regression analysis using the Eviews 11 application. The secondary data used is sourced from the Central Statistics Agency, the Ministry of Education and Culture Data Statistics, and the 2015-2019 Regional Education Balance. Partially, the results state that the labor force has a positive and significant effect on the education budget, the literacy rate has a positive and significant effect on the education budget, and the dropouts rate has a negative but not significant effect on the education budget. Furthermore, there is a significant simultaneous effect between the labor force, literacy rate, dropouts rate on education budget disparities.